Cognitive Neuroscience Neuroimaging Repository for the Adult Lifespan - Razlighi, Qolamreza R. (Neuroimage, 2015)
With recent advances in neuroimaging technology, it is now possible to image human brain function in vivo, which revolutionized the cognitive neuroscience field. However, like any other newly developed techniques, the acquisition of neuroimaging data is costly and logistically challenging. Furthermore studying human cognition requires acquiring a large amount of neuroimaging data, which might not be feasible to do by every researcher in the field. Here, we describe efforts in our group to acquire one of the largest neuroimaging datasets that aims to investigate neural substrates of age-related cognitive decline, which will be made available to share with other investigators. Our neuroimaging repository includes up to 14 different functional images for more than 486 subjects across the entire adult lifespan in addition to their 3 structural images. Currently, data from 234 participants have been acquired, including all the 14 functional and 3 structural images which is planned to be increased to 375 participants in the next few years. A complete battery of neuropsychological tests was also administered to all participants. The neuroimaging and the accompanying psychometric data will be available through an on-line and easy to use data sharing website.